Impact of Communication Behaviour of Farmers of Watershed areas in central India - Om Prakash (Journal of Agricultural Extension Management, 2025)
The degraded land is estimated to be about 178 million hectares in the country. The total arable dryland / rainfed land is under a constant degradation process, the degree of variation being from moderate to severe level of erosion. The reason for soil erosion in drylands is due to many, varied and complex factors, which include not only biophysical factors but also socio-economic factors. The socio-economic factors are totally neglected to improve degraded natural factors such as land, water and vegetation (Sastry et al. 2004). Hence, the Government of India initiated watershed development programme during 1983-84 to improve natural factors so as to improve the economic conditions of farmers and this programme has been continuing till date with sufficient allotment of funds in the budget. A research project was undertaken to know the impact of watershed on natural factors for the benefit of administrators, policy makers etc